2017
DOI: 10.2147/ott.s139686
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the anticancer effects of a novel proteasome inhibitor, ixazomib, on colorectal cancer using a combined method of microarray and bioinformatics analysis

Abstract: PurposeThe study aimed to explore the anticancer effects of a novel proteasome inhibitor, ixazomib, on colorectal cancer (CRC) using a combined method of microarray and bioinformatics analysis.Materials and methodsCell proliferation was tested by Cell Counting Kit-8 (CCK-8) assay for SW620 cells treated with different concentrations of ixazomib and different treatment times. The microarray analysis was conducted for six samples, including three samples of SW620 cells untreated with ixazomib and three samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…Therefore, we proposed that by induction of these key factors, hyperthermia has the potential to interfere with HPV DNA replication and expression as well as HPV antigen presentation and, in this way, boost the immunologic clearance of HPV infections. Usually, proteins within the same interaction module possess similar functions [37], and the GO-BP enrichment analysis of the two major interaction modules mined from the PPI-network revealed a highly similar functional involvement as compared to those identified by clustering, indicating that the interaction modules mined from the PPI network were crucial to the overall proteomic changes that result from hyperthermia, and therefore worthed further attention and more detailed investigations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, we proposed that by induction of these key factors, hyperthermia has the potential to interfere with HPV DNA replication and expression as well as HPV antigen presentation and, in this way, boost the immunologic clearance of HPV infections. Usually, proteins within the same interaction module possess similar functions [37], and the GO-BP enrichment analysis of the two major interaction modules mined from the PPI-network revealed a highly similar functional involvement as compared to those identified by clustering, indicating that the interaction modules mined from the PPI network were crucial to the overall proteomic changes that result from hyperthermia, and therefore worthed further attention and more detailed investigations.…”
Section: Discussionmentioning
confidence: 97%
“…The grayscale analysis of western blot results was shown in barplot (L). CA samples were assigned to either 37 C control group (37) or 44 C hyperthermia (44). Asterisk ( Ã ) indicates statistically significant differences between the hyperthermia and control groups, whereas ns indicates non-significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors can cause apoptosis, mainly through protein accumulation-mediated cellular stress or proteotoxicity [ 1 , 3 , 4 ]. Several proteasome inhibitors have been approved by the FDA or are undergoing clinical and pre-clinical studies for cancer therapy [ 5 10 ]. The primary applications of proteasome inhibitors in cancer therapy are for the treatment of multiple myeloma or mantle cell lymphoma [ 2 , 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While bortezomib is only approved to treat of multiple myeloma and mantle cell lymphoma, multiple studies have shown that the use of bortezomib in concert with other chemotherapeutics can significantly increase cell death in solid tumors [ 8 – 10 , 15 , 16 ]. Ixazomib is another reversible boronate proteasome inhibitor, which recently gained clinical approval for treatment of multiple myeloma, and has also shown the ability to inhibit proliferation and induce apoptosis in solid tumors [ 2 , 3 , 5 , 12 ]. On the other hand, carfilzomib, is a potent irreversible proteasome inhibitor approved for treatment of multiple myeloma, especially in patients who didn’t respond well to previous treatment with bortezomib [ 2 , 3 , 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 Previously studies reported that ixazomib induces apoptosis in a verity of cancers including liver cance, 11 melanom 12 and CR. 13,14 The above unique features of ixazomib may help to maintain optimal serum concentrations of ixazomib and improve treatment convenience for the patient.…”
Section: Introductionmentioning
confidence: 99%